Feasibility of Average Photon Energy (APE) in performance evaluation of PV modules equipped with IR reflecting filter - Fetliński, Bartosz; Kieliszczyk, Marcin; Janaszek, Bartosz (Photonics Letters of Poland, 2024)
In this work, we investigate the feasibility of the APE (Average Photon Energy) parameter as a qualitative representation of solar spectra in modeling the performance of PV modules equipped with a filter capable of reflecting parasitic IR irradiance. We evaluate APEs’ relation with parasitical absorption of solar irradiance in the structure of PV modules (glass, lamination foil, back sheet), as well as its relation to the calculated temperature of PV modules operating in standard conditions. In our analysis, we employ real-world data of spectral irradiance. Full Text: PDF References B.S. Richards, A. Ivaturi, S.K.W. MacDougall, J. Marques-Hueso, "Up- and down-conversion materials for photovoltaic devices", Proc. SPIE 8438, 843802 (2012), CrossRef A. Ibrahim, M.Y. Othman, M.H. Ruslan, S. Mat, K. Sopian, "Recent advances in flat plate photovoltaic/thermal (PV/T) solar collectors", Renew. Sustain. Ener. Rev. 15, 352 (2011), CrossRef N. Khorrami, M.R. Zargarabadi, M. Dehghan, "A novel spectrally selective radiation shield for cooling a photovoltaic module", Sustain. Ener. Technol. Assess. 46, 101269 (2021), CrossRef G. Nofuentes, C.A. Gueymard, J. Aguilera, M.D. Pérez-Godoy, F. Charte, "Is the average photon energy a unique characteristic of the spectral distribution of global irradiance?", Solar Energy 149, 32(2017), CrossRef A. Andreas, T. Stoffel, NREL Solar Radiation Research Laboratory (SRRL): Baseline Measurement System (BMS), Golden, Colorado (Data), NREL Report No. DA-5500-56488 (1981). CrossRef